2014
DOI: 10.1016/j.prevetmed.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis in Northern Ireland: Risk factors associated with time from post-outbreak test to subsequent herd breakdown

Abstract: Compulsory bovine Tuberculosis testing has been implemented since 1959 in NorthernIreland. Initial rapid progress in the eradication of the disease was followed by a situation where disease levels tended to fluctuate around a low level. This study Tuberculin Test (SICTT) reactors at disclosure test), local bTB prevalence, herd size and type were identified as significant risk factors (p<0.05), as was the purchase of higher numbers (n>27 per year) of cattle. Consistent with other studies this work shows bTB con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
(48 reference statements)
7
21
1
Order By: Relevance
“…We purposely used a simple metric for a history of bTB infection (similar to [3]) as we only wanted to control for this known risk factor. However, we acknowledge that the relationship between current risk and previous history may be complex, and highlight other more in-depth analysis of this issue [37,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…We purposely used a simple metric for a history of bTB infection (similar to [3]) as we only wanted to control for this known risk factor. However, we acknowledge that the relationship between current risk and previous history may be complex, and highlight other more in-depth analysis of this issue [37,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…In Italy, enterprises consisting of both dairy and beef animals, presented a greater risk [odds ratio (OR) 4•92, 95% CI 1 •26-19•19] than exclusively dairy enterprises, attributed to differences in purchasing policy [78]. Dairy herds experienced a recurrent bTB incident sooner than non-dairy herds in Northern Ireland, even after controlling for herd size [82], but a similar study in Ireland showed that dairy animals had a lower risk of a future restriction [83]. GB surveillance data indicate that the relationship between bTB incidence rate and herd type may be a result of the larger sizes of dairy herds and their location [84].…”
Section: Herd Typementioning
confidence: 99%
“…However, dairy herds have been found to be a risk factor for herd bTB breakdown and the risk of recurrence in Northern Ireland (Doyle et al, 2014), and of increased risk of disclosing a LRS in the Republic of Ireland (Olea-Popelka et al, 2008). O'Hagan et al (2015) looked at the probability of SCITT positive animals being confirmed with bacteriology in NI, and found that dairy herds were significantly more likely to be confirmed than non-diary.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This indicates that the dairy herds may be particularly vulnerable to having SCITT tests that underperform both in their ability to detect true positives and false negatives (O'Hagan et al, 2015). This problem of non-detection of truly infected dairy animals may be a partial explanation for the shorter times to breakdown observed in such herds in NI, as it may represent within-herd residual infection (Doyle et al, 2014;Lahuerta-Marin et al, 2015). Moreover, it has been described that bTB can spread faster in dairy herds than in beef herds (Alvarez et al, 2012b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation